Benzene and Naphthalene Degrading Bacterial Communities in an Oil Sands Tailings Pond - Rochman, Fauziah F.; Sheremet, Andriy; Tamas, Ivica; Saidi-Mehrabad, Alireza; Kim, Joong-Jae; Dong, Xiaoli; Sensen, Christoph W.; Gieg, Lisa M.; Dunfield, Peter F. (Frontiers in Microbiology, 2017)
Oil sands process-affected water (OSPW), produced by surface-mining of oil sands in Canada, is alkaline and contains high concentrations of salts, metals, naphthenic acids, and polycyclic aromatic compounds. Residual hydrocarbon biodegradation occurs naturally, but little is known about the hydrocarbon-degrading microbial communities present in OSPW. In this study, aerobic oxidation of benzene and naphthalene in the surface layer of an oil sands tailings pond were measured. The potential oxidation rates were 4.3 μmol L-1 OSPW d-1 for benzene and 21.4 μmol L-1 OSPW d-1 for naphthalene. To identify benzene and naphthalene-degrading microbial communities, metagenomics was combined with stable isotope probing (SIP), high-throughput sequencing of 16S rRNA gene amplicons, and isolation of microbial strains. SIP using 13C-benzene and 13C-naphthalene detected strains of the genera Methyloversatilis and Zavarzinia as the main benzene degraders, while strains belonging to the family Chromatiaceae and the genus Thauera were the main naphthalene degraders. Metagenomic analysis revealed a diversity of genes encoding oxygenases active against aromatic compounds. Although these genes apparently belonged to many phylogenetically diverse taxa, only a few of these taxa were predominant in the SIP experiments. This suggested that many members of the community are adapted to consuming other aromatic compounds, or are active only under specific conditions.